Handwriting analysis as an assessment instrument in legal psychology - Chernov, Yury; Engalychev, Vali (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Handwriting analysis has several advantages important for legal psychology over traditional instruments. However, being a projective method, it must be well validated.The article presents a formal system of psychological handwriting analysis, which allows an objective and transparent procedure and in particular ensures conditions for proper validation. Practical examples demonstrate that.
Keywords: handwriting psychology; formal handwriting analysis; computer application; legal psychology; validation